RAG on Multimodal Databases: Orchestrating Textual, Vector, and Graph-based Retrieval - Xavier, Otávio Calaça; Soares, Anderson da Silva (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2025)
This tutorial explores contemporary Information Retrieval (IR) techniques for building RAG systems from a multimodal database perspective. We cover the implementation of textual retrieval (e.g., Full-Text Search), the rise of vector search with native extensions (e.g., pg_vector, ChromaDB), and the use of Knowledge Graphs with Cypher/GQL. Focusing on the challenge of hybrid search, the course presents evaluation metrics (e.g., Recall@K, MRR, NDCG@K) and relevance fusion techniques such as Reciprocal Rank Fusion (RRF). Finally, we demonstrate the construction of an end-to-end RAG pipeline that orchestrates these multiple data sources to augment an LLM. Participants will learn how to design and implement hybrid retrieval systems to enrich text generation with relevant, structured, and verifiable data.